Design and fabrication of flexible DNA polymer cocoons to encapsulate live cells - Tao Gao (Nature Portfolio, 2019)
The ability to encapsulate living cells could lead to many applications. Here, the authors present a flexible method to graft DNA polymers onto bacteria, yeast and mammalian cells, polymerize them into DNA cocoons and use these to manipulate and select cells based on the encoded polymer sequences on DNA cocoons.